the Analysis of Electronic Medical Record Implementation in the Administrative Processs of the Beauty Clinic X: nalysis of Electronic Medical Record Implementation in the Administrative Processs of the Beauty Clinic X - Aszahra, Jisha Syariffa; Parimita, Widya; Rachmadania, Rizki Firdausi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
In the rapidly advancing era of globalization, the healthcare sector is increasingly integrating information technology to enhance operational efficiency. This research investigates the implementation of Electronic Medical Records (EMRs) in the administrative processes of Beauty Clinic X. The study aims to understand the extent of EMR usage, identify obstacles encountered during implementation, and explore efforts to overcome these challenges. Data were collected through interviews, observations, and documentation, with both primary and secondary sources providing comprehensive insights. The findings reveal that the transition from manual to electronic systems presents significant challenges, including user difficulties and inefficiencies in the patient administration process. Despite these obstacles, the study highlights the potential benefits of EMRs in facilitating the preparation of financial reports, enabling online delivery of receipts, and allowing patients to access their own medical information through the SATUSEHAT platform. This research contributes to the existing literature by focusing on beauty clinics, providing insights and recommendations for optimizing EMR use in similar healthcare facilities.